Estudo de revisão e prospecção biotecnológica das espécies Passiflora alata Curtis e Passiflora edulis Sims - MESQUITA, Ludmilla Santos Silva de (2019)
Passiflora alata Curtis and Passiflora edulis Sims (Passifloraceae), known as sweet and sour passion fruit, respectively, are plant species widely used in folk medicine and by food and pharmaceutical industries. They have a broad spectrum of biological activities, mainly attributed to their secondary metabolites. For industrial purposes, the use of plant extracts requires standardization, which evaluates the variables that influence the stability of the chemical composition and consequently the desired action. Considering the need of natural products with antioxidant activity and molluscicidal agents that contribute to the reduction of schistosomiasis in the world, this work aimed to standardize extracts of the leaves of Passiflora edulis; to evaluate the chemical composition and molluscicidal activity of Passiflora alata leaf extracts in Biomphalaria glabrata as well as the toxicity to non-target organisms, Artemia salina and Danio rerio. In the review of the literature on P. alata and P. edulis was reported the identification and isolation of various compounds, especially the classes of flavonoids, saponins, terpenes and cyanogenic glycosides; for the extracts of P. alata and P. edulis, several biological activities mainly related to action on the central nervous system were demonstrated; variations in chemical composition and biological action were observed among studies that used extracts prepared in different ways; the studies validate the popular use and point out the technological potential of these two plant species. In the standardization study of P. edulis extracts was employed three different extractive methods and drug:solvent ratio, after the extracts were evaluated for the content of phenolic compounds and flavonoids, antioxidant activity by the in vitro assay with 2,2-diphenyl-1-picrylhydrazyl (DPPH) and the iron reducing capacity (FRAP). Phenolic content varied between 11.98 and 16.30% and flavonoid content between 2.49 and 4.11%; the extract with the highest content of phenolic compounds and flavonoids, as well as antioxidant activity was obtained by maceration in the 1: 8 hydromodule. Chemical analysis of this extract revealed the presence of flavonoids, of which six C-glycosylated flavones and one O-glycosylated flavone. The results of the evaluation of molluscicidal activity of leaf extract and fractions of P. alata are in third part of this thesis, where median lethal concentrations (LC50) were obtained for B. glabrata of 28.6, 14.3 and 8.7 mg L-1, for the aqueous extract, butanolic fraction and ethyl acetate fraction, respectively. In general, the samples showed low toxicity for A. salina and D. rerio. Flavonoids were identified in all analyzed samples, and the saponin quadranguloside in the aqueous extract and butanolic fraction. As a result of this work was filed patent application of molluscicidal product based on plant extract of P. alata leaves. Therefore, the review study evidenced the need of standardization of Passiflora extracts; it was demonstrated that the extraction method and the drug:solvent ratio influence the quality of P. edulis leaves extracts; the results showed for the first time the possibility of using P. alata leaves for the production of molluscicidal agents to be used in control of B. glabrata snail, intermediate host of the parasite Schistosoma mansoni.